Giuliana GIUSTI. Nominal Syntax at the Interfaces: a Comparative Analysis of Languages with Articles. Cambridge. Cambridge Scholars Publishing. 2015. 235 pp. ISBN (10) 1-4438-8024-8 - Brito, Ana Maria (Linguística: Revista de Estudos Linguísticos da Universidade do Porto, 2018)
.